Neonatal enteric complex in andean alpacas - Rosadio A., Raúl (2012)
Advances in research on the major causative agents of morbidity and mortality in newborn alpacas associated with enteric processes in southern Peru were reviewed. Microbiology and molecular analyses performed on intestinal samples from enterotoxemia fatalities confirmed the predominance of C. perfringens type A carrying only the gene coding for the major α exotoxin and identifiying for the first time the presence of the novel β2 toxin gene. In vitro studies have yielded three profiles for phospholipase activity (high, medium and low) with biological activity when high and medium strains were inoculated intraintestinally in mice and rabbits, but did not induce intestinal pathology in an alpaca cria. A detailed histopathological investigation has reveled that within necrotizing hemorrhagic enteritis Clostridium coexist with massive presence of Eimeria macusaniensis suggesting that primary parasite tissue destruction may well predispose overgrowth of clostridium and toxin production, triggering enteric fatalities. Additionally, studies on diarrheas intestinal swabs and/or intestinal contents identified Escherichia coli pathogenic strains (enteropathogenic and enterohemorrhagic). The immunofluorescent direct test and PCR revealed the presence of Giardia intestinalis coexisting with mostly enteropathogenic and enterohemorrhagic E. coli strains, as well as with a virus similar to bovine coronavirus. These microbes are potentially diarrheagenic pathogens and a possible infection source for Andean people.